Special functions - Wang, Z. X.; Guo, D. R. (Singapore : World Scientific, 1989)
In this book, expansions of functions in infinite series and infinite product and the asymptotic expansion of functions are discussed. This may be the best reference book on Special Functions.
Includes bibliographical references.
Keywords: Functions; Gamma funtion; Hypergeometric function; Bessel function